Implementation of SRR Loaded Frequency Reconfigurable Antenna for 5G and IoT Wireless Applications - Mayer, Afshan Nabi; Ashraf, Shazia; Sheikh, Javaid A.; Balkhi, Altaf A. (IEEE Uttar Pradesh Section International Conference on Electrical, Computer and Electronics (Online), 2023)
Reconfigurable antennas are viable for communication including Internet of Things (IoT) systems that demand to be less expensive, more compact, and effective as compared to conventional smart antennas. The proposed design offers multiband functionality and increases the system's adaptability by altering its frequency characteristics subject to the requirements. Through reconfigurability, the hardware intricacy, design time, the number of resonant constituents and cost can be reduced. A frequency reconfigurable microstrip patch antenna is presented having a small size of 30×30 × 1.6 mm 3 . The antenna operates in four distinct modes with the assistance of two pin diode switches The suggested antenna operates in the 2.9-9.5 GHz band and resonates at various frequencies including 2.9 GHz, 4.2 GHz, 6GHz, 7.2 GHz, 8.2 GHz, 8.8 GHz, and 9.5 GHz based on the PIN diodes' switching state. The proposed antenna's gain ranges from 5.77 to 6.11 dBi.